Long-Run Impacts of In-Utero Ramadan Exposure: Evidence from Administrative Tax Records - Timotej Cejka; Mazhar Waseem (Center for Economic Studies and ifo Institute (CESifo), 2022)
Using Ramadan fasting as a natural experiment, we estimate the long-run impacts of in-utero health and nutrition shocks on adult outcomes. We exploit administrative tax return data comprising the universe of income tax returns filed in Pakistan during 2007–2009. The data allow us to link in-utero Ramadan exposure of individuals with their later life labor market outcomes. We find a robust negative effect of Ramadan exposure on earnings (a lower-bound estimate of around 2–3 percent). The exposed individuals are less likely to be in high-skilled occupations and less likely to be in the top of the income distribution. Using nationally representative survey data we show that our results are unlikely to be driven by selective timing of conception.
Keywords: I15; J13; J24; 330; nutrition shock; human capital; labor market outcomes